2021
DOI: 10.3390/agronomy11030522
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Leaf Cuticular Transpiration and Growth Traits in Field-Grown Wheat and Aegilops Genetic Resources

Abstract: Plants are subjected to unregulated water loss from their surface by cuticular transpiration. Therefore, specific morphophysiological changes may occur during leaf development to eliminate water loss. This study aimed to examine the cuticular transpiration of 23 winter wheat genotypes and their wild-growing predecessors of the genus Aegilops, which were divided into three groups to demonstrate their diversity. The genotypes were sown in autumn and grown in regular field trials at the Research Institute of Plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…Similarly, the highest reduction in seed germination and growth traits was recorded under -1.2 MPa osmotic potential level compared to the control treatment of the study which supported our second hypothesis [14,38]. Seed germination is an important transition stage from seeds to seedlings for crop plants and higher seed germination under stressful and benign environmental conditions enable plants to thrive and produce higher yields under adverse as well as benign environments [38]. Seed germination is controlled by the microclimatic conditions of the seedbed as well genetic potential of the crop plants.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, the highest reduction in seed germination and growth traits was recorded under -1.2 MPa osmotic potential level compared to the control treatment of the study which supported our second hypothesis [14,38]. Seed germination is an important transition stage from seeds to seedlings for crop plants and higher seed germination under stressful and benign environmental conditions enable plants to thrive and produce higher yields under adverse as well as benign environments [38]. Seed germination is controlled by the microclimatic conditions of the seedbed as well genetic potential of the crop plants.…”
Section: Discussionsupporting
confidence: 83%
“…According to this study, most of the landraces fall under area type that is due to the extensive leaf area, while modern cultivars showed high stomatal conductance which is the basis for high dry matter per unit leaf area. On the other hand, cuticular transpiration is a type transpiration under circumstance of maximum stomata closure and acting as a predictor of drought resistance [98,99]. Though it was not considered in this study, further investigations are needed to identify the effect of cuticular transpiration per unit of leaf area on plants water consumption in the future.…”
Section: Discussionmentioning
confidence: 98%
“…The variability of g min can be also driven by stomatal morphology (leaky stomata) or chemical composition of cuticle ( Duursma et al 2019 ; Machado et al 2021 ). In a recent study across 23 genotypes of wheat, cuticular transpiration showed a strong positive correlation with water loss per dry mass unit, which the authors considered as a proxy for WUE bio ( Gašparovič et al 2021 ). A modelling simulation approach by Duursma et al (2019) revealed a theoretical reduction of WUE i under increasing g min of plants using the general Ball-Berry model of stomatal conductance.…”
Section: Water Side Of Wuementioning
confidence: 99%